Small-scale gold mining operations in Benguet and Camarines Norte, Philippines - Clemente, Eligia D.; Lanticse, Leslie Joy G.
Small-scale gold mining in the Philippines has been practiced since the early 1900s. Today, however, with more than 100,000 families currently involved in the operation, more "modern" methods have been employed. A more sophisticated system for mining the ore has been developed, and gold production is being done through amalgamation. Inspite of the low efficiency of the method and the hazards to health, the people find amalgamation the most convenient method in terms of economics. This paper reports the activities connected with the recovery of gold in the small scale mining communities in Benguet and Camarines Norte.
Keywords: Gold mines and mining -- Philippines